Matemática financeira : uma proposta de sequência didática para o ensino médio - Favero, André Luiz (2024)
Financial Mathematics should be a fundamental field of the mathematics of high school, given the everyday human need to analyze and make decisions regarding the use of money and future planning. Its importance goes far beyond the school environment; it is essential in the personal, professional, and social lives of individuals. However, data show a high level of indebtedness in Brazil, and most people still keep their savings in low-interest accounts, reflecting a lack of financial organization and knowledge about the financial market and investment opportunities. Most likely, many of these individuals, like myself, did not receive financial education, either at home or in school. In this regard, this dissertation presents the development of a Didactic Sequence aimed at teaching financial mathematics in high school, with the objective of connecting the content with students’ everyday lives through a practical and interactive approach. The created Didactic Sequence includes topics such as financial organization, percentages, simple and compound interest, rate conversions, saving methods, payment options, the financial market, investments, and loans, exploring each concept through activities that involve real-life situations. By working through this sequence, it is hoped that students will develop calculation skills, critical thinking, and a better understanding of financial concepts, along with an improved ability to apply these concepts in real-life situations. Thus, this dissertation aims to provide substantial material for mathematics teachers to approach financial mathematics in a way that is both relevant and engaging for students